Factors Associated with Hypothermia Post Spinal Anesthesia in the Central Surgical Installation in 2023 - Janner Manurung; Ahmad Tajudin (West Science Interdisciplinary Studies, 2023)
Hypothermy is a condition in which the body's temperature-delivering mechanism has difficulty coping with the stress of cold temperatures. Hypothermy can also mean that the temperature of body parts is below 36 0C (Potter & Perry 2015). In spinal anesthesia will lower the threshold of shivering to the hypothermic core in the first hour or after spinal anesthesia will decrease by about 1-2oC. Shivering usually occurs in the intraoperative period until the postoperative period. The incidence rate varies greatly between 5% and 65%, It is associated with the redistribution of body heat from the core compartment to the periphery and causes hypothermy (Alfonsi, 2009).